2022
DOI: 10.1101/2022.06.15.496280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased severity of chronic kidney disease in response to high potassium intake is dependent on mineralocorticoid receptor activation

Abstract: Dietary treatment is seminal for management of chronic kidney disease (CKD). The aim of our project was to assess the effects of potassium intake on the progression of CKD. We used 2 mouse CKD models to analyze the effects of potassium intake on CKD : the unilateral ureteral obstruction (UUO) and the POD-ATTAC models. POD-ATTAC mice display a podocyte-specific apoptosis after the administration of a chemical inducer. We also studied the effect of mineralocorticoid receptor (MR) using UUO in kidney tubule-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…The kidney injury pattern in rats with CKD on the high K + diets was different from the low K + diet in the sense that it was characterized by increased collagen deposition without a clear influx of macrophages or T cells. A recent study in two different mouse models of CKD showed that K + -induced fibrosis is dependent on the mineralocorticoid receptor [ 58 ]. This suggests a role for the K + -induced rise in plasma aldosterone, which is also supported by the strong correlation between plasma aldosterone and collagen deposition.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney injury pattern in rats with CKD on the high K + diets was different from the low K + diet in the sense that it was characterized by increased collagen deposition without a clear influx of macrophages or T cells. A recent study in two different mouse models of CKD showed that K + -induced fibrosis is dependent on the mineralocorticoid receptor [ 58 ]. This suggests a role for the K + -induced rise in plasma aldosterone, which is also supported by the strong correlation between plasma aldosterone and collagen deposition.…”
Section: Discussionmentioning
confidence: 99%